Penginderaan Jauh 3D DEM untuk Klasifikasi Geomorfologi Daerah Mandolang Sulawesi Utara - Afiat Anugrahadi; Ramadhan Adhitama; Djordy Imanuel Liusvia; Yusraida Khairani Dalimunthe (LPPM Institut Teknologi Petroleum Balongan, 2025)
Remote sensing using satellites is an efficient and successful alternative for conducting geomorphological studies as important earth information. Known as a tourist area for its beaches and natural water baths. making the research location in the Mandolang District, Minahasa Regency, North Sulawesi Province important to research. In this study, a different approach to geomorphological studies was used: DEM data for 3D analysis was used to see various geomorphological images. Bird's eye views from a variety of locations and directions can be provided by the 3D DEM model, which can also obtain height and slope information from Topographic Maps and Slope Maps. The results of the map analysis are then used to produce a descriptive Geomorphological Map where the research area is dominated by a height of 175-350m above sea level and based [19] classification. The research area has three geomorphological units: 21% covers plains with height differences 0-50m and steepness 0-15%; 63.2% covers waves with height differences 50-200m and steepness 15-45%; and 63.2% covers hilly area with height differences 350-500m and steepness more than 45%.